Polyphenol extract of Syzygium brachythyrsum mitigates atherosclerosis in high-fat diet induced ApoE-/- mice by regulating ROS/Keap1/Nrf2 pathway - He-Ping Liu; Pei-Wen He; Kai-Jing Yu; Qiang Shang; Wen Xu; Xin-Fu Cai (PLoS ONE, 2026)
Syzygium brachythyrsum (SB) is an ethnic herb widely used by the Dai ethnic minority in Yunnan province of China. Our previous studies have shown that the polyphenol extract of SB (PSB) exhibits antioxidant and anti-inflammatory effects, and inhibits the formation of macrophage-derived foam cells by reducing lipid uptake and inflammation, suppressing reactive oxygen species (ROS), and downregulating the NF-κB and MAPK signaling pathways. This study aims to investigate the effects of PSB on suppressing atherosclerosis in vivo and to explore the underlying mechanisms.A high-fat diet was used to induce the development of atherosclerosis in ApoE -/- mice for 12 weeks. Mice were treated with three doses of PSB and atorvastatin. Morphological characteristics of aorta bulk, aortic root and liver were examined using Oil Red O and H&E staining. ELISA, immunofluorescence and fluorescence staining were used to assess lipid level, pro-inflammatory cytokines, oxidative indexes, ROS levels and CD36 protein expression in the aortic root. In vitro, an ox-LDL-induced THP-1 macrophage-derived foam cell model was established. ROS fluorescence and Western blot analyses were performed to investigate the involvement of the ROS/Keap1/Nrf2 signaling pathway, with or without the Nrf2 inhibitor ML385. The Results suggested that PSB significantly reduced lipid plaques in the aorta, and hepatic lipid accumulation. PSB also improved serum and hepatic lipid profiles and inflammatory levels, alleviated oxidative stress and reduced CD36 expression in vivo. Furthermore PSB inhibited ox-LDL induced foam cell formation, alleviated the stimulation of oxidative stress in THP-1 foam cells by activating the ROS/Keap1/Nrf2 signaling pathway. These effects were blocked by the Nrf2 inhibitor ML385.For the first time, our study revealed the anti-atherosclerotic effects of polyphenol extract of S. brachythyrsum . It offers insight into the potential mechanism by which PSB mitigates the early onset of AS via ROS/Keap1/Nrf2 pathway. In summary, the current study suggests that PSB, as a complementary therapy, may have a beneficial effects on cardiovascular diseases and deserves further investigation.